Analisis Hubungan Karakteristik Individu dengan Jaringan Komunikasi Petani Karet Pola Swadaya di Desa Lubuk Terentang - Ilham Kurniawan; Eri Sayamar; Roza Yulida (Politeknik Pertanian Negeri Payakumbuh, 2021)
The purpose of this study is to describe the characteristics of individual rubber farmer self-help pattern in Lubuk Terentang Village and analyze the relationship between individual characteristics of farmers with communication networks in spreading farming information. Gunung Toar is a district famous for its rubber plantations which can be seen from the consistency of its farmers in producing and marketing their products through rubber auctions. most related to the communication network of farmers formed in the progress of rubber farming in the Lubuk Terentang Village. This research was conducted using snowball sampling to find the actors involved. Furthermore, the actors involved are measured by three communication network indicators namely local centrality, global centrality and togetherness. The next, individual characteristics are tested with Spearman Rank correlation. The results of this study describe the age of farmers in the category of capable and educated, have family dependents and experienced in difficult fields, land area and the level of moderate category of cosmopolitan. While the intensity of counseling, the accuracy of extension channels and the number of sources of information are in the high category. The characteristics of individual farmers who have a relationship with communication network indicators are age, education, family responsibilities, farming experience, land area, cosmopolitanism, intensity of counseling, accuracy of extension channels, and the number of sources of information.